Animal cruelty and the development of “link” research between nonhuman and human violence - Tallichet, Suzanne E. (Animal abuse and interpersonal violence, 2024)
This chapter reviews the development of the scholarly study of the link between animal cruelty and interpersonal violence. Previous research is discussed with a particular focus on the effects of animal cruelty motives and methods, including bestiality, on later human violence. Theories used to explain animal cruelty and its causal connection with human violence are also reviewed, namely, social learning theory (including the frustration hypothesis and differential association theory), the sexually polymorphous theory, and violence graduation and deviance generalization hypotheses. Each theory is discussed in light of existing empirical studies. We conclude with a summary of these implications for understanding the link and suggestions for future research based on past limitations and promising new topical areas for study.